Hot electron–driven tandem CO 2 reduction and propane dehydrogenation over plasmonic black gold nanoreactors - Gunjan Sharma; Charvi Singhvi; Girish Mishra; Amitabha Nandi; Götz Schuck; Nico Grimm; Dirk Wallacher; Abhishek Kumar; Pavan Nukala; Sukhendu Nath; Soumya Ghosh; Vivek Polshettiwar (Proceedings of the National Academy of Sciences, 2025)
Catalytic CO 2 reduction into value-added products is an energy-intensive process and typically relies on molecular hydrogen as reductant. Coupling CO 2 reduction with propane dehydrogenation for in situ hydrogen generation presents a sustainable alternative but conventionally demands high temperatures, causing undesirable side reactions such as cracking and coke formation. Here, we demonstrate a nonthermal catalytic pathway driven by hot electrons generated via localized surface plasmon resonance. Using a plasmonic catalyst comprising Ga–Ni–Mn active sites anchored on broadband plasmonic “black gold,” we achieve tandem CO 2 reduction and propane dehydrogenation under visible-light irradiation. The catalyst consistently produces equimolar amounts (~1,600 µmol g −1 h −1 ) of CO and propene under flow conditions, maintaining exceptional stability even after 500 h. Notably, light illumination suppresses undesired side reactions, such as dry reforming of propane, cracking, and coking, preserving a stable stoichiometric ratio of CO and propene. Mechanistic studies, including controlled thermal experiments, Arrhenius analysis, and finite-difference time-domain simulations, confirm that catalytic selectivity and stability originate specifically from plasmon-induced hot electrons rather than photothermal effects. Comprehensive structural characterization using X-ray absorption near-edge structure and extended X-ray absorption fine structure, in situ diffuse reflectance infrared Fourier transform spectroscopy, ultrafast transient absorption spectroscopy, and density functional theory calculations elucidate that plasmonic excitation promotes advantageous charge-transfer states within Ga–Ni–Mn ensembles, facilitating selective activation of CO 2 and propane. This study establishes hot electron–driven plasmonic catalysis as a distinctive strategy for tandem propane dehydrogenation and circular CO 2 utilization under mild conditions.